A Comprehensive Investigation of Deep Drawing Processes for a 2-Inch Diameter Dop-pipe Cap: Numerical and Experimental Analysis - Tikamori, Ghazi; Patya, Dhea Intan; Sukarman, Sukarman; Aulia Nanda, Rizki; Mulyadi, Dodi; Khoirudin, Khoirudin; Amir, Amir; Rokhman, Taufiqur; Safril, Safril (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2024)
The persistent challenges in material forming processes arise from recurrent issues encountered during the deep drawing process, particularly involving cracks and deviations from standard thickness dimensions. This article investigates the deep drawing process using both experimental and numerical methodologies. The experimental approach employs a 40-ton capacity power press machine, while the numerical method utilizes the ABAQUS student version software. SPCC-SD (JIS G3141) is the selected material for producing a Dop-pipe 2-inch diameter pipe cap in both approaches. Noteworthy findings include the highest positive and negative correlations observed in elements E 46 and E 48, with values of 0.715 and -0.933, respectively. Minimal disparities, averaging around 4.6% for all components, were evident between the experimental and numerical methodologies. The numerical approach yielded predictive results identifying potential issues in elements E 47 and E 48. This observation did not reveal instances of tearing failure but instead showcased an increase in thickness due to a higher axial force between the dies and punched-in components. The study successfully and accurately predicted product thickness for all components, presenting a contrast with outcomes obtained through the experimental method. Furthermore, this research advances the deep drawing process, extending its applicability to broader material forming applications and ultimately enhancing overall production process efficiency.